The Effect Of Merger And Acquisition On Financial Performance Per Company In Manufacturing Companies Listed On The IDX 2017-2021 - Rachman, Rachmawaty; Kartika, Diamond; Marlina, Tri (Institut Bisnis dan Informatika Kesatuan, 2025)
Most of the companies work hard to expand the business in a various ways in order to remain established and generate profits. The company owner and manager has an interest to increasing company’s financial performance. Company restructurion is a method that can be implemented by companies so that the company's financial performance can grow, which can be done using various techniques, which is expansion techniques are one of them. Business expansion is an effort to develop a business which can be carried out by means of mergers and acquisitions. The purpose of this research was to determine there were influence of merger and acquisition on financial performance which is current ratio, debt to equity ratio, total aset turnover, net profit margin, return on equity, and earning per share. The researchers did research to manufacture companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling method used was purposive sampling, which resulted 19 manufacture companies as a research sample. The result of research analysis using Kolmogorov Smirnov showed that data not normally distributed, because the value of asymp. Sig (2-tailed) is smaller or equal to 0,05. The hypothesis data test using the Wilcoxon signed rank test because the financial performance before and after merger and acquisition showed an asymp. Sig (2-tailed) is smaller or equal to 0,05. The hypothesis test result showed that there are significant differences in return on equity after companies did merger and acquisition. While, in total asset turnover, current ratio, debt to equity ratio, net profit margin, and earning per share there is no significant differences after companies did merger and acquisition. Keywords : financial performance, merger, acquisition, financial ratio